FORMULASI DAN EVALUASI SABUN PADAT DENGAN PENAMBAHAN YOGHURT SEBAGAI ANTIOKSIDAN - Yola Desnera Putri; Ledianasari Ledianasari; Giani Nurrahmawati (PHRASE (Pharmaceutical Science) Journal, 2023)
Soap was used to clean the skin but not damage the skin and able to protect skin from free radical effect. The compounds that could counteract free radical are antioxidants which can be found in yoghurt. The purpose of this research was to determine the formula and evaluation of solid soap with the addition of yoghurt according to the SNI 2016 requirements. The methods used are making yoghurt, evaluating yoghurt, testing the antioxidant activity of yoghurt, formulating solid soap, and evaluating solid soap. Solid soaps F1, F2, F3, F4 with yoghurt concentrations were 2; 2.5; 3; 3.5. The evaluation results of solid soaps from yoghurt to the four formulas had good results, namely water content, insoluble material in ethanol, free fatty acids, and chloride levels that met the SNI 2016 requirements. The evaluation of the antioxidant activity test showed that the yoghurt was 57.87 µg / mL with the category strong and of the four solid soap formulas only F1 and F4 still have strong antioxidant activity. F1 with antioxidant activity of 98.81 µg / mL in the strong category, and F4 with antioxidant activity of 82.36 µg / mL in the strong category.